Society Perspective on the Greatness of Walisongo (Library Analysis Study on Walisongo) - Irsad Fadilah; Budi Haryanto (ISTAWA, 2021)
This study aims to investigate the facts regarding the factors regarding to constitute the society perspective in glorifying Walisongo. With the da'wah strategy of the Sunans, which began and was widely accepted by Javanese people at that time, many generations made Walisongo as the charismatic figure examples. Thus, it is feared that the society will adhere to previous community rules which acculturated to Hindu culture and forget the Islamic rules based on the Prophet guidance. The society's perspective on Walisongo revolves around that the wali are the ancestry of Prophet Muhammad, the descendants of the king and have the great powers. The roots of the formation of a community perspective regarding the greatness of Walisongo such as paternalistic society, unwilling to learn and bound by maintained family traditions. Based on the literature review, it was found that Walisongo was an ordinary human being and stories about supernatural powers and karomah were affixes stories that were added by parents to their children in the past which eventually formed the crystallization.